Effect of Deformable Baffle on the Mixed Convection of Non- Newtonian Fluids in a Channel-Cavity - Yaseen, Duna T.; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2020)
A simulation of fluid-structure interaction (FSI) and combined convective heat exchange is accomplished in an open trapezoidal cavity-channel. A non-Newtonian (power law fluid) is inspected within the laminar region. The heat source is simulated by an isothermal hot cavity bottom wall, whereas all the rest solid walls are perfectly insulated. A deformable baffle is fixed at the top wall of the channel and its free end extends towards the open cavity. The location of the deformable baffle on the top wall is varied. The baffle position is investigated together with Richardson number ($Ri = 0.01-100$) and power law index ($n = 0.5-1.5$). The problem was solved using finite element method with Arbitrary Lagrangian-Eulerian (ALE) technique. The results are compared with the non-baffled channel. The study shows that the proposed baffled channel enhances the heat transfer notably.